The - Watts, Niki (Oxford University Press, 1997)
The Oxford Paperback Greek Dictionary is a completely new reference work designed to meet the needs of both English and Greek speakers in the 1990s. With over 45,000 words and phrases it provides fully up-to-date coverage of the general vocabulary of contemporary Greek and English, in a clear and accessible form. Idiomatic phrases illustrate words in use, and there are full explanations of terms for which cultural differences prevent an exact translation